Música y sociedad en el capitalismo tardío - Moench, Eric (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This paper studies a transitional period of music located between the 1920 and 1940. But not as an end in itself, but to dive into the musical philosophy of Theodor Adorno, the author who lived immersed in late capitalist societies, context without which none of his work can be understood. Adorno´s aesthetics stresses that art should have its own purpose and, at a time, one aim of the social order of need, this is their dual nature which prevents analyzing the work of art only in its immanence. From this perspective, try to answer the following questions: ¿What is the relationship between music and society? ¿Are there political effects generated by the music? And finally ¿what are the critical potential that involve music?